Inhibition of SARS-CoV-2 3CL protease by the anti-viral chimeric protein RetroMAD1 - Chan, Lee-Chin; Mat Yassim, Aini Syahida; Ahmad Fuaad, Abdullah Al Hadi; Leow, Thean Chor; Sabri, Suriana; Radin Yahaya, Radin Shafierul; Abu Bakar, Awang Muhammad Sagaf (Nature Research, 2023)
COVID-19 results from SARS-CoV-2, which mutates frequently, challenging current treatments. Therefore, it is critical to develop new therapeutic drugs against this disease. This study explores the interaction between SARS-CoV-2 3CLpro and RetroMAD1, a well-characterized coronavirus protein and potential drug target, using in-silico methods. The analysis through the HDOCK server showed stable complex formation with a binding energy of -12.3, the lowest among reference drugs. The RetroMAD1-3CLpro complex underwent a 100 ns molecular dynamics simulation (MDS) in an explicit solvation system, generating various trajectories, including RMSD, RMSF, hydrogen bonding, radius of gyration, and ligand binding energy. MDS results confirmed intact interactions within the RetroMAD1-3CLpro complex during simulations. In vitro experiments validated RetroMAD1's ability to inhibit 3CLpro enzyme activity and prevent SARS-CoV-2 infection in human bronchial cells. RetroMAD1 exhibited antiviral efficacy comparable to Remdesivir without cytotoxicity at effective concentrations. These results suggest RetroMAD1 as a potential drug candidate against SARS-CoV-2, warranting further in vivo and clinical studies to assess its efficiency.